2009
DOI: 10.1152/ajpcell.00641.2008
|View full text |Cite
|
Sign up to set email alerts
|

Fasting enhances the response of arcuate neuropeptide Y-glucose-inhibited neurons to decreased extracellular glucose

Abstract: Fasting increases neuropeptide Y (NPY) expression, peptide levels, and the excitability of NPY-expressing neurons in the hypothalamic arcuate (ARC) nucleus. A subpopulation of ARC-NPY neurons ( approximately 40%) are glucose-inhibited (GI)-type glucose-sensing neurons. Hence, they depolarize in response to decreased glucose. Because fasting enhances NPY neurotransmission, we propose that during fasting, GI neurons depolarize in response to smaller decreases in glucose. This increased excitation in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
83
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 43 publications
6
83
0
Order By: Relevance
“…A possible cellular mechanism underlying the changes in food and glucose intake is increased activity of arcuate NPY neurons, since there were changes in release of NPY in response to glucose from ex vivo hypothalamic slices from iARC-GK rats. As has been reported previously (55), increasing glucose concentrations in the artificial CSF (aCSF) resulted in reduced NPY release from control hypothalami. In contrast, there was no decrease in NPY release from iARC-GK hypothalami with increasing glucose concentrations.…”
Section: Discussionsupporting
confidence: 61%
“…A possible cellular mechanism underlying the changes in food and glucose intake is increased activity of arcuate NPY neurons, since there were changes in release of NPY in response to glucose from ex vivo hypothalamic slices from iARC-GK rats. As has been reported previously (55), increasing glucose concentrations in the artificial CSF (aCSF) resulted in reduced NPY release from control hypothalami. In contrast, there was no decrease in NPY release from iARC-GK hypothalami with increasing glucose concentrations.…”
Section: Discussionsupporting
confidence: 61%
“…How L-type calcium channel potentiation affects the firing properties of NPY neurons is a very interesting question. NPY neurons are sensitive to energy status, and previous studies have revealed that AMPK activity controls excitation of NPY/agouti-related protein neurons (Murphy et al, 2009;Kohno et al, 2011). We hypothesize that L-type channel potentiation increased the frequency of action potentials via activation of AMPK.…”
mentioning
confidence: 70%
“…For example, adiponectin increases food intake by activating AMPK in the arcuate hypothalamus (Kubota et al, 2007;Wen et al, 2010), and ghrelin promotes feeding through a mechanism involving the short-term activation of hypothalamic AMPK (Lopez et al, 2008). Accumulated evidence indicates that AMPK in NPY neurons senses hunger signals and shifts energy homeostasis toward increased food intake (Murphy et al, 2009;Kohno et al, 2011). For instance, decreased leptin and glucose after fasting activated AMPK in glucose-inhibited NPY neurons and increased neuron excitation, which led to NPY release and food intake (Murphy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knockout of mice AMPKα2 induces the responses to changes in extracellular glucose levels in NPY neurons [13] . The change in action potential can be stimulated by AMPK activator AICAR and blocked by AMPK inhibitor compound C [14][15][16] . Decreased glucose activates AMPK and elevates [Ca 2+ ] i in NPY neurons [15] .…”
Section: Introductionmentioning
confidence: 99%